TEACHER – STUDENT INTERACTION AND MOTIVATION IN LANGUAGE LEARNING - Aziza Safaralieva (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2025)
This paper explores the crucial role of teacher–student interaction in motivating learners in English as a Foreign Language (EFL) classrooms. It argues that the quality of communication, empathy, and feedback between teachers and students significantly influences learners’ engagement and performance. The study emphasizes that motivation is not only a psychological factor but also a product of effective pedagogical relationships.